Location-inventory-routing model with considering urban road networks - Nova Indah Saragih; Senator Nur Bahagia; Suprayogi Suprayogi; Ibnu Syabri (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: To develop LIRP (location-inventory-routing problem) model with considering multiple links and solve it using method of heuristic based on algorithm of simulated annealing. Method of heuristic for the LIRP model is applied in city of Jakarta to improve effectiveness and efficiency of the food supply chain. Design/methodology/approach: The LIRP model is developed using main references. To solve the model, this paper develops two methods, namely method of optimal and method of heuristic. Computational experiments are performed to obtain the efficiency of the method of heuristic. New design of food supply chain is resulted from the application of the method of heuristic in city of Jakarta. Findings: The new design of food supply chain resulted from the application of LIRP model in city of Jakarta reduces total cost by 18%, increases availability from 76% to 95%, and reduces the number of vehicles by 73%. This paper also shows that distance is not the only consideration to decide the traversed links in cities. Research limitations/implications: Average gap between method of heuristic and method of optimal in terms of total cost is 3.1%. Practical implications: Government of city of Jakarta can improve effectiveness and efficiency of the food supply chain by implementing the LIRP model. Social implications: Citizens of Jakarta are well provided with their needs of vegetables and fruits. Originality/value: The first LIRP model that considers multiple links to represent road networks in cities. The LIRP model developed in this paper consists of probabilistic demands, multi products, and multi echelons. Traditional markets, UCCs (urban consolidation centers) and province of suppliers are the places where decisions of inventory made.
Keywords: 650; cost of congestion; LIRP model; method of heuristic; road networks; simulated annealing